Enhancing the Analysis of Eu 3+ Photoluminescence in Coordination Compounds in the Solid State by Determining their Refractive Index - Sedykh, Alexander E.; Maxeiner, Moritz; Seuffert, Marcel T.; Heuler, Dominik; Kurth, Dirk G.; Müller-Buschbaum, Klaus; Justus Liebig University Giessen (My University, 2024)
This study is focused on determining the refractive index as a crucial parameter for evaluating the intrinsic quantum yield and the ligand sensitisation efficiency in solid-state trivalent lanthanide coordination compounds. For this, eight trivalent europium complexes with phenyl-terpyridine ([EuX3(ptpy)(L)], X=Cl− or NO3−, ptpy=4′-phenyl-2,2′ : 6′,2′′-terpyridine, L=H2O or other molecules) were examined. Their refractive indices were determined using the Becke lines test by immersing transparent material in a series of media with known refractive indices. Using the set of media presented here, determining crystalline materials′ refractive indices from 1.41 to 1.73 with a step of 0.01 is possible. Assessment of the refractive indices of the complexes mentioned above allowed a comprehensive analysis of their photophysical properties in the solid state. Moreover, this method can be extrapolated for other solid-state materials, offering valuable insights in the broader field of photophysics. In addition to photoluminescence investigations, the compounds presented were characterised by single-crystal X-ray diffraction (SCXRD), powder X-ray diffraction (PXRD), Hirschfeld surface area analysis, UV-Vis reflectance spectroscopy, hydrolysis sensitivity analysis, and simultaneous thermogravimetry and differential thermal analysis coupled with mass-spectrometry (STA-MS).
Keywords: ddc:540